Solomon Islands : 2016 Article IV Consultation and Fifth and Sixth Reviews Under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Solomon Islands. (IMF Staff Country Reports; Country Report ;, 2016)
This paper presents an overview of Solomon Islands' economy. Although Solomon Islands is a small island state, low-income country that is severely affected by external shocks, including commodity price declines, natural disasters, and climate change, it has achieved considerable gains in terms of macroeconomic stability under the Extended Credit Facility program. Despite the low access, the program has been effective in catalyzing donor support. Economic growth in 2015 is estimated at 3u percent. Near-term prospects remain favorable but new sources of growth are needed over the medium term. Key policy recommendations have been discussed in the paper to further strengthen the economy of Solomon Islands.